Improving Graphic Design Competence of Vocational Students through Graphic Design Skills of Yapim Biru Biru Private Vocational School Students - Hita Hita; Salsalina Br Sembiring; Djoni Djoni; Hanes Hanes; Culita Culita (Jurnal IPTEK Bagi Masyarakat, 2026)
SMK Swasta Yapim Biru Biru is a vocational high school located on Jl. Besar Delitua–Medan, Aji Baho, Sibiru-biru District, Deli Serdang Regency, North Sumatra, operating under the auspices of the Ministry of Education and Culture. The school aims to produce highly competent students who can compete in the globalization era; therefore, students are expected to develop creativity and technological skills essential for their future careers. One activity supporting this goal is the use of Adobe Photoshop to enhance practical skills. This community service program provided Adobe Photoshop training to help students create aesthetic and engaging visual content, implemented through training sessions followed by pre-test and post-test evaluations. The results showed that students achieved higher scores on the post-test compared to the pre-test, indicating improved understanding, and it is hoped that this program will further motivate students to deepen their knowledge of Adobe Photoshop and develop the creativity needed in the digital era.